Marilyn Monroe sings "Happy Birthday Mr President" (Module II, 2013)
USA. New York, Madison Square Gardens. Peter Lawford (actor) introduces actress Marilyn Monroe as Monroe walks on the stage (wearing fur stole and glittering gown) introducing her as "Mr President, the late Marilyn". Monroe Monroe stands at microphone shading eyes to see audience before performing "Happy Birthday" for US President J F Kennedy. A giant birthday cake is carried along on to the stage to the sound of the orchestra playing "Happy Birthday". John F Kennedy (US President) walks on to the stage and annouces: "I can now retire from politics after having had 'Happy Birthday' sung to me in such a sweet fashion". Footage moves back to Monroe standing at microphone being introduced by Peter Lawford.